Impaired KIN10 function restores developmental defects in the Arabidopsis trehalose 6-phosphate synthase1 (tps1) mutant - Zacharaki, Vasiliki (The New phytologist, 2022)
© 2022 The Authors New Phytologist © 2022 New Phytologist Foundation.